2007
DOI: 10.1103/physrevb.75.075415
|View full text |Cite
|
Sign up to set email alerts
|

Predictions for the formation of atomic chains in mechanically controllable break-junction experiments

Abstract: We analyze the stability and magnetic properties of infinite zigzag atomic chains of a large number of late third, fourth and fifth-row transition metal atoms, as well as of the Group IV elements Si, Ge, Sn and Pb. We find that zigzag chains of third-and fourth-row elements are not stable, while those made of Si, Ge, Sn, Pb, W, Os, Ir, Pt and Au are. These results correlate well with known data in Mechanically Controllable Break Junction experiemnts (MCBJE). We therefore conjecture that the stability of an inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 32 publications
11
49
1
1
Order By: Relevance
“…[13]. This implementation has been tested satisfactorily in several bulk semiconductors and metals [13], some molecular magnets [14], a large number of atomic chains [15] and a good number of small metallic (in the present work) and intermetallic clusters [14] by now. We have crosschecked our results for Ir 2 and Pt 2,3 with the plane-wave, Vanderbilt pseudopotentials code Quantum ESPRESSO [16].…”
mentioning
confidence: 79%
“…[13]. This implementation has been tested satisfactorily in several bulk semiconductors and metals [13], some molecular magnets [14], a large number of atomic chains [15] and a good number of small metallic (in the present work) and intermetallic clusters [14] by now. We have crosschecked our results for Ir 2 and Pt 2,3 with the plane-wave, Vanderbilt pseudopotentials code Quantum ESPRESSO [16].…”
mentioning
confidence: 79%
“…It is, therefore, of interest to investigate possible ferromagnetic (FM) and antiferromagnetic (AF) magnetization in the linear chains of all 4d and 5d transition metals including Y, Zr, Nb, La, Hf and Ta zigzag chain which appear not to have been considered. As mentioned before, recent ab initio calculations indicate that the zigzag chain structure of, at least, Zr 23 , Ir 16 , Pt 16 and Au 16,25 , is energetically more favorable than the linear chain structure. Thus, we also study the structural, electronic and magnetic properties of all 4d and 5d transition metal zigzag chains in order to understand how the physical properties of the monoatomic chains evolve as their structures change from the linear to zigzag chain.…”
Section: Introductionmentioning
confidence: 72%
“…16. Surprisingly, the second energy minimum state in the Nb, Mo, Tc, W and Re chains (Table V) is in fact the global energy minimum, i.e., its total energy is below the corresponding minimum energy listed in Table IV.…”
Section: The Zrmentioning
confidence: 88%
See 1 more Smart Citation
“…Nanoparticles of Pt are often used as a catalyst, for instance in catalytic converters in automobiles and in fuel cells, where the size of these nanoparticles is an important parameter [69]. A more recent development in the research of Pt has been the discovery that it is one of three metals found to form monoatomic chains, along with Au and Ir [1,[70][71][72][73]. During the last decade, theoretical investigations on such atomic-sized Pt contacts have predicted the emergence of magnetism in such small structures [74][75][76].…”
Section: Potential Magnetism In Atomic-sized Pt Contactsmentioning
confidence: 99%